Makna Komunikasi Persuasif Muallim Darul Tafsir Terhadap Santri - Amir Hamzah; A. Khairuddin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
Persuasive communication is a process of delivering messages from the communicator to the communicant to change beliefs, attitudes and behavior by influencing the psychological aspects of the communicant. This study aims to determine the meaning of persuasive communication by converts to students in the Darul Tafseer Boarding School of Salafiyah Safi’iyah Sukorejo Islamic Boarding School. This research is a qualitative research with a case study research model. The results of the research on the meaning of persuasive communication between Muslim and darul tafsir, are building intimacy, eliminating the saturation of the students, providing freedom about where to study, building a fun learning process, building motivation, maintaining the basic principles of forming a darul tafsir dormitory according to the rules of the Islamic boarding school, providing punishment for students darul tafsir, improve the quality of the ability of students, maintain the existence of darul interpretation, increase the seriousness of students in recitation of the book, increase the understanding of students on the basis of carrying out an activity, increase mastery of the yellow book